STRATEGI PENGEMBANGAN DESTINASI WISATA PANTAI OLELE KABUPATEN BONE BOLANGO DALAM MENDUKUNG PARIWISATA BERKELANJUTAN - Nue Eng Mokodompit; Ramlah Alkatiri; Sri Hantuti Paramata; Joice Machmud (LPPM Universitas Muhammadiyah Gorontalo, 2026)
Tourism has become one of the strategic sectors capable of stimulating regional economic growth, generating employment opportunities, and improving community welfare through the sustainable utilization of local resources. Marine tourism destinations with unique natural resources require comprehensive development strategies that integrate environmental conservation, community participation, destination governance, and infrastructure improvement. Olele Beach in Bone Bolango Regency is recognized as one of Gorontalo Province's leading marine tourism destinations because of its internationally renowned coral reef ecosystem and rich marine biodiversity. Despite its considerable tourism potential, the destination continues to face several challenges, including inadequate tourism amenities, limited destination management, insufficient digital promotion, and the need to strengthen institutional and community capacity. This study aims to formulate a sustainable development strategy for Olele Beach tourism destination by integrating SWOT analysis with the perspectives of Destination Development Theory, Sustainable Tourism, and Community-Based Tourism. A qualitative descriptive approach was employed through field observations, in-depth interviews, documentation, and SWOT analysis involving relevant stakeholders. The findings indicate that Olele Beach possesses significant internal strengths and external opportunities, positioning the destination within the Strengths–Opportunities (SO) quadrant, which supports a growth-oriented development strategy. The priority strategies include improving tourism amenities and governance, strengthening community participation, expanding digital tourism promotion, conserving coastal ecosystems, and enhancing collaboration among government, local communities, and tourism stakeholders. These findings contribute to a more comprehensive framework for sustainable marine tourism development by integrating strategic planning, destination governance, and community empowerment to improve destination competitiveness while ensuring long-term environmental sustainability